2020
DOI: 10.7717/peerj.8698
|View full text |Cite
|
Sign up to set email alerts
|

Postcranial anatomy and histology ofSeymouria, and the terrestriality of seymouriamorphs

Abstract: Seymouria is the best known of the seymouriamorphs, a group of Permo-Carboniferous reptiliomorphs with both terrestrial and aquatic taxa. The majority of research on Seymouria has focused on cranial anatomy, with few detailed descriptions or illustrations of the postcrania. We utilized neutron computed tomography (nCT) and histological sampling to provide updated, detailed figures that clarify details of the postcranial anatomy and to assess the development and histology of Seymouria through specimens from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Bazzana et al . 2020 also confirmed the rapid metamorphosis of Seymouria , in contrast to Discosauriscus , by using histological sampling. Additionally, a study of 3D bone histology showed that S. sanjuanensis and D. austriacus had relatively rapid bone growth and dynamics in contrast to Devonian stem‐tetrapods and temnospondyls of equal size.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Bazzana et al . 2020 also confirmed the rapid metamorphosis of Seymouria , in contrast to Discosauriscus , by using histological sampling. Additionally, a study of 3D bone histology showed that S. sanjuanensis and D. austriacus had relatively rapid bone growth and dynamics in contrast to Devonian stem‐tetrapods and temnospondyls of equal size.…”
Section: Discussionsupporting
confidence: 67%
“…The absence of skeletal remains pertaining to adult individuals of discosauriscids in the lacustrine deposits of the Boskovice Basin also appears to be best explained by a biphasic life cycle: a shift in their habitat occupancy from an aquatic to a terrestrial setting during ontogenetic development, which is also assumed for Seymouria (Berman 2000; Eberth et al . 2000; Bazzana 2020) and Karpinskiosaurus (Klembara 2011). Furthermore, the presence of a single discosauriscid individual that could represent an early adult stage (SNM Z 25814) indicates that the habitat shift occurred around the age of 10 years or possibly slightly earlier in most individuals, given that SNM Z 25814 already lacks the sensory grooves (Klembara 2009 b ).…”
Section: Discussionmentioning
confidence: 99%
“…While early tetrapods are often compared to modern amphibians (e.g., Clack, 2012; Molnar et al, 2020; Sanchez, de Ricqlès, et al, 2010; Sanchez & Klembara, 2008), there are discrepancies in body size and the extremely derived life histories of modern amphibians likely confounds many morphological and/or physiological comparisons of growth through ontogeny. Thus, the applicability of this comparison remains questionable (Bazzana et al, 2020), and we broaden our modern vertebrate group comparison in deciphering likely explanations for the avascular zone, all while acknowledging the limitation of drawing comparisons between Greererpeton and modern taxa. Given these constraints, in our consideration of possible life history events, we establish the following criteria determined by the bone histology observed in our sample: (1) the event must incur reduced bone deposition and/or metabolic stress, (2) it must happen after limb ossification is initiated but well before skeletal maturity, and (3) it must occur as a singular event that is not repeated during the lifetime of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…With some exception (Laurin et al, 2007; Meunier & Laurin, 2012), these analyses have been conducted on the humerus, an element that is taxonomically informative for these groups yet is highly disparate from the morphology of modern tetrapod limb bones that have been used to validate paleohistological interpretations (Castanet et al, 2000; De Margerie et al, 2002; Margerie et al, 2004; Montes et al, 2007). Permian crown tetrapods, on the other hand, have been extensively sampled and have demonstrated a wide range of established ecologies and life history strategies (e.g., Bazzana et al, 2020; Boitsova et al, 2019; Estefa et al, 2020; Gee, Haridy & Reisz, 2020; Huttenlocker & Shelton, 2020; Konietzko‐Meier et al, 2016; Sanchez & Klembara, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…whether they are linked to their early relatives through a line of terrestrial ancestors (see e.g., discussion in Bazzana et al, 2020).…”
Section: Evolutionary Stages Of Ancestral Amniote Locomotion and Trackmaker Model For The Lcaamentioning
confidence: 99%